TRANSPARANSI PENGUNAAN DANA DESA DALAM PEMBANGUNAN MAHYANI DI DESA LELATO KECAMATAN SUMALATA KABUPATEN GORONTALO UTARA - Suprapto, Srihandayani; Ayuba, Maharani (JSAP : Journal Syariah and Accounting Public, 2020)
This research aims to determine the transparency of the use of village funds in Mahyani development in Lelato Village, Sumalata District, North Gorontalo District. The research method used is a qualitative approach with descriptive research type. The results showed that the transparency of the use of village funds in mahyani development was not in accordance with what was expected. Of the three indicators to measure the level of transparency, there is one indicator that has worked well, namely the indicator of the ease of obtaining information. Meanwhile, two indicators that have not been going well are openness, where there is still a need for transparency on the mahyani development mechanism which often raises public perceptions. Then on the indicators of regulations and procedures, there is still a need for socialization about regulations related to mahyani development so that it does not cause a decrease in public trust in the village government